2004
DOI: 10.1111/j.1440-1754.2004.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diclofenac sodium ingestion and severe neonatal pulmonary hypertension

Abstract: We describe a case of severe pulmonary hypertension and transient right-sided hypertrophic cardiomyopathy in a neonate, caused by premature closure of ductus arteriosus after short-term maternal use of diclofenac sodium (Voltaren). In view of this associated complication, diclofenac sodium should be avoided during pregnancy. In addition, maternal diclofenac sodium ingestion should be suspected if a newborn develops severe pulmonary hypertension and/or right-sided hypertrophic cardiomyoptathy with closed ductus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…Entre os anti-inflamatórios, destaca-se a relação entre utilização materna de diclofenaco na gestação e o desenvolvimento de hipertensão pulmonar severa, causando lesão isquêmica irreversível do músculo papilar de um recém-nascido 18 , bem como a ocorrência de cardiomiopatia hipertrófica transitória do lado direito causada pelo fechamento prematuro do canal arterial após o uso materno de diclofenaco sódico 19 . Um estudo sugere o aumento do risco de constrição do canal arterial em neonatos após a ingestão materna de doses orais de nimesulida 14 .…”
Section: Introductionunclassified
“…Entre os anti-inflamatórios, destaca-se a relação entre utilização materna de diclofenaco na gestação e o desenvolvimento de hipertensão pulmonar severa, causando lesão isquêmica irreversível do músculo papilar de um recém-nascido 18 , bem como a ocorrência de cardiomiopatia hipertrófica transitória do lado direito causada pelo fechamento prematuro do canal arterial após o uso materno de diclofenaco sódico 19 . Um estudo sugere o aumento do risco de constrição do canal arterial em neonatos após a ingestão materna de doses orais de nimesulida 14 .…”
Section: Introductionunclassified
“…17 There are reports of use of potentially harm full drugs 1.5% to 4.8% during pregnancy from developed and under developed countries of the world. 3,[18][19][20] In a retrospective register-based cohort study, it was found that 20.4% women purchase at least one drug classified as clearly harmful. 21 Many women can be exposed to drugs (mainly non steroidal anti inflammatory drugs) that can leads to some risk during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal DS consumption should be avoided during pregnancy since the newborn may be affected by severe pulmonary hypertension and hypertrophic cardiomyopathy with closed ductus arteriosus [24]. Inan et al showed that DS has a side effect of bursting pressures of the colonic anastomoses and hydroxyproline content of the perianastomotic tissue in rats [11].…”
Section: Discussionmentioning
confidence: 99%